2020
DOI: 10.3390/ma13173874
|View full text |Cite
|
Sign up to set email alerts
|

Customized 3D-Printed Titanium Mesh Developed to Regenerate a Complex Bone Defect in the Aesthetic Zone: A Case Report Approached with a Fully Digital Workflow

Abstract: Alveolar-ridge augmentation, anterior aesthetics, and digital technologies are probably the most popular topics in the dental-implant field. The aim of this report is to present a clinical case of severe atrophy of the anterior maxilla in a younger female patient, treated with a titanium membrane customized with computer-aided design/computer-aided manufacturing (CAD/CAM), simultaneous guided implant placement, and a fully digital workflow. A young female patient with a history of maxillary trauma was treated … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
32
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7
1
1

Relationship

2
7

Authors

Journals

citations
Cited by 27 publications
(32 citation statements)
references
References 16 publications
0
32
0
Order By: Relevance
“…To date, the CAD/CAM technology has been implemented to produce various types of dental restorations including inlays, onlays, crowns, veneers, multi-unit fixed partial dentures (FPDs), and implant abutments [ 1 , 2 ]. Moreover, the CAD/CAM technology has expanded its dental applications to comprise orthodontic treatment, fabrication of occlusal splints, fabrication of removable dentures and maxillofacial prostheses, guided implant surgery, orthognathic surgery, and guided bone regeneration [ 6 , 7 , 8 , 9 , 10 , 11 , 12 , 13 , 14 , 15 ]. This innovative technology is still evolving with growing and promising applications in the dental field.…”
Section: Introductionmentioning
confidence: 99%
“…To date, the CAD/CAM technology has been implemented to produce various types of dental restorations including inlays, onlays, crowns, veneers, multi-unit fixed partial dentures (FPDs), and implant abutments [ 1 , 2 ]. Moreover, the CAD/CAM technology has expanded its dental applications to comprise orthodontic treatment, fabrication of occlusal splints, fabrication of removable dentures and maxillofacial prostheses, guided implant surgery, orthognathic surgery, and guided bone regeneration [ 6 , 7 , 8 , 9 , 10 , 11 , 12 , 13 , 14 , 15 ]. This innovative technology is still evolving with growing and promising applications in the dental field.…”
Section: Introductionmentioning
confidence: 99%
“…As demonstrated by several studies, pilot‐drill implant placement showed inferior accuracy than fully‐guided implant placement 19‐23 . However, in case of simultaneous implant placement and guided bone regeneration, the pilot‐drill guide protocol, that controlled the pilot drilling only, could be recommend 14‐16 . Using a pilot‐drill surgical template with metallic sleeve may allow to maintain drill guidance, leading to place the implant in the correct, prosthetically driven position, compensating the possible small distortion caused by the heat treatment.…”
Section: Discussionmentioning
confidence: 99%
“…For the latter, guided surgery has been suggested in combination with guided bone regeneration. The main benefits to combine these approaches are related to the three‐dimensional diagnosis and the prosthetically driven implant placement 14‐16 . On the contrary, the main limitation is related to the lack of guidelines for cleaning and disinfection of the surgical templates used in combination with major surgical procedures.…”
Section: Introductionmentioning
confidence: 99%
“…Data reported in the present study are consistent with other report. (19)(20)(21) On the contrary, immediate loading and the placement of a definitive abutment the day of the implant insertion and never removed, have been proven to reduce MBL. (22,23) A possible explanation could be that, in the present research, most of the immediately loaded implants were placed flapless, using guided surgery, and received the definitive abutment on the day of surgery, minimizing MBL.…”
Section: Discussionmentioning
confidence: 99%